Cyclobutylamino-naphthalimide-based fluorescent probe for detection of glutathione in living cells - Das S.; Goswami P.; Indurthi H.K.; Koch B.; Sharma D.K. (My University, 2025)
Fluorophores that incorporate cyclobutylamine auxochromes exhibit improved quantum yields, photostability, biocompatibility, and cell permeability. In this study, we present the design and synthesis of a novel ratiometric probe (NAPB) based on cyclobutylamino-naphthalimide (NCB), which enables the selective and sensitive detection of glutathione (GSH). NAPB employs a nucleophilic substitution/cyclization strategy to detect GSH. In the presence of GSH, a noticeable ratiometric change in the emission wavelength occurs, shifting from blue to greenish-yellow fluorescence. The probe can detect GSH rapidly, with a detection limit as low as 39.1 nM. Following confirmation of biosafety through an MTT assay, NAPB was further utilised for fluorescence imaging of GSH in live HepG2 cells. © 2025 Elsevier B.V.